Pelatihan Pemanfaatan Artificial Intelligences Quillbot dalam Menurunkan Plagiasi Karya Ilmiah bagi Mahasiswa Baru - Khoiri, Moh; Safar, Muh.; Haddar, Gamar Al; Hanum, Gilang Kartika; Rukiyanto, Bernardus Agus (Universitas Pahlawan Tuanku Tambusai, 2026)
This Community Service Program (PKM) aims to train new students in utilizing the Quillbot Artificial Intelligence application as a tool to reduce plagiarism in scientific works. The implementation method of this research consists of three main stages, namely: (1) Preparation Stage, including needs analysis through an initial survey and preparation of training materials; (2) Implementation Stage, carried out through training seminars with interactive lecture methods, direct demonstrations of the use of Quillbot features (such as paraphraser, summarizer, and grammar checker), as well as practice and mentoring (coaching clinic); and (3). The results of the study indicate that this training succeeded in significantly improving the understanding and skills of participants. Participants' knowledge of responsible paraphrasing techniques increased by an average of 75%. Furthermore, during the practical session, participants were able to reduce the plagiarism rate in the given example texts from an average of 80% to below 15%, while maintaining academic integrity and the original meaning of the referenced sources. The conclusion of this activity is that structured training on the use of the AI Quillbot, oriented towards academic ethics, effectively empowers new students to produce more original writing and avoid plagiarism.